Self-assembly synthesis of petal-like MoS2/Co9S8/carbon nanohybrids for enhanced lithium storage performance - Wu, Bo; Ma, Ran; Liu, Xuewei; Zheng, Yuqi; Guo, Sisheng; Yi, Yanmeng; Sun, Mingtai; Wang, Suhua; Wen, Tao (Frontiers in Energy Research, 2022)
Transition metal sulfides are favored as anode materials for the next generation of lithium-ion batteries because of their high theoretical capacities and abundant natural resources. However, serious volume changes during charging and discharging pose great challenges to their stability. In this work, petal-like MoS2/Co9S8/C nanohybrids were synthesized via the immobilization of molybdyl acetoacetonate MoO2(acac)2 in ZIF-67 and subsequent combined vulcanization and thermolysis process. Benefiting from the homogeneous bimetallic sulfide and highly conductive carbon layer, the as-obtained MoS2/Co9S8/C nanohybrids exhibited a high initial discharge capacity of 988.3 mAh g−1 at 200 mA g−1 and a capacity retention > 99.9% after 50 cycles. Even at a high current density of 1000 mA g−1, the reversible capacity of MoS2/Co9S8/C is still as high as 754.6 mAh g−1, revealing extraordinary rate ability. This work can provide a general approach to design and synthesize other advanced bimetallic chalcogenides for boosting lithium-ion batteries storage performance.